Manajemen Kurikulum dalam Meningkatkan Mutu Pembelajaran di SMPN 40 Surabaya - Fatiqh, Sonata Al; Mujahidah, Atika; Wati, Nehha Kusuma (ARZUSIN, 2023)
This research aims to analyze the role of curriculum management in enhancing the quality of education at SMPN 40 Surabaya. The research methodology employed a case study approach with data collection through interviews, observations, and document analysis. The findings indicate that effective curriculum management plays a crucial role in optimizing resource utilization, identifying learning needs, and measuring learning outcomes. With proficient curriculum management, schools can design more relevant and efficient teaching and learning processes, improve the quality of teaching by educators, and enhance student learning achievements. The results of this research provide valuable insights for SMPN 40 Surabaya and other educational institutions in their efforts to improve the quality of education by prioritizing effective curriculum management.